Analisis Dampak Inflasi Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 1992-2022 - Alfaddli, Mhd; Satria, Doni (Universitas Negeri Padang, 2024)
This research aims to determine and analyze the extent of the influence of inflation on economic growth in Indonesia, by considering control variables that influence economic growth. This research is descriptive and inductive research. The data used is time series data in Indonesia for the period 1992 to 2022 which was obtained from the World Bank. This research uses cointegration testing and qudratic non-linier regression analysis to determine the impact of inflation on economic growth in Indonesia. From the results of the cointegration test, inflation has a linear influence on economic growth. From the regression results, inflation simultaneously has a significant effect on economic growth. Partially, inflation has a positive and significant influence on economic growth, but at a certain point, inflation has a negative and significant influence on economic growth in Indonesia